James Joyce a powieść hipertekstowa. Perspektywa dialogiczna i eksperyment narracyjny - Bandrowska, Olha (ANNALES UNIVERSITATIS PAEDAGOGICAE CRACOVIENSIS. STUDIA LINGUISTICA, 2012)
The paper focuses on tradition and those 20th century interpretations of tradition in which it is understood as an essential factor in modern culture and literature. The author’s standpoint is that the concept of trans-discursivity broadens the understanding of tradition since, according to Michel Foucault, a writer or a scholar in the position of trans-discursivity produces not just paradigmatic rules for the formation of texts within the defined discourse boundaries but opens up a possibility of creating texts that, although conceptually different from the original type of discourse, nevertheless maintain relevance to it. It has been demonstrated that the innovations introduced by James Joyce in his Ulysses and Finnegans Wake allow the reader to approach his works in terms of trans-discursivity. Contemporary American hypernovels, Afternoon: A Story by Michael Joyce and Victory Garden by Stuart Moulthrop, provide ample evidence to support this claim given that their openness and rhizomatic, non-linear character of their narratives is rooted in the Joycean tradition of discursivity.